2005
DOI: 10.1207/s15430154jce2003_10
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Screening Attitudes and Continuing Education Needs of Primary Care Physicians

Abstract: Physicians are supportive of the value of screening, however the reliability of and evidence to support DRE and PSA as prostate cancer screening tests are in question. CME which addresses issues surrounding prostate screening and areas related to patient education and counselling are of greatest need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 7 publications
2
33
0
3
Order By: Relevance
“…Applying the inclusion and exclusion criteria, 929 were excluded on the basis of the title and abstract (Kappa: 0.90) and 160 on the basis of the full text (Kappa: 0.95). Twenty articles were retained: 14 studies analysing the PCP's point of view [24][25][26][27][28][29][30][31][32][33][34][35][36][37] , 5 studies analysing the patient's point of view [38][39][40][41][42] , one study analysing both. 43 3.1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying the inclusion and exclusion criteria, 929 were excluded on the basis of the title and abstract (Kappa: 0.90) and 160 on the basis of the full text (Kappa: 0.95). Twenty articles were retained: 14 studies analysing the PCP's point of view [24][25][26][27][28][29][30][31][32][33][34][35][36][37] , 5 studies analysing the patient's point of view [38][39][40][41][42] , one study analysing both. 43 3.1.…”
Section: Resultsmentioning
confidence: 99%
“…26,31,33,34,37 Physicians reported high and rising rates of PSA testing from 1993 to 1998. 34 The number of PCPs recommending PSA testing of healthy men is also high in Canada (87.5% 28 last year. 41 Reported PSA screening rates were lower (24%) in the Australian study among patients 40 years of age and older.…”
Section: Pcps' Self-reported Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a survey of 485 family physicians in Newfoundland and Labrador, Curran and colleagues found that although most respondents screened men 50 and older, there were divergent beliefs about the benefits of prostate cancer screening. 25 This study has notable limitations. Selection bias is possible since physicians with strong opinions on the subject may have been more likely to participate.…”
Section: Prostate Cancer Screening In Ontariomentioning
confidence: 94%
“…It is likely that the results can be extrapolated to the rest of the country, as these findings have been corroborated by other papers addressing the same question in Newfoundland and British Columbia. 11,12 Most importantly, the survey shows the need not only to provide clear and evidence-based guidelines, but also for better education on prostate cancer screening for family physicians. A significant onus of responsibility for this lies with our own association and members.…”
mentioning
confidence: 99%